[123I]β-CIT SPECT is a useful method for monitoring dopaminergic degeneration in early stage Parkinson's disease. Issue 3 (1st March 2003) - Winogrodzka, A; Bergmans, P; Booij, J; van Royen, E A; Stoof, J C; Wolters, E C
Abstract : Objectives: To examine the validity of [ 123 I]β-CIT SPECT for monitoring the progression of dopaminergic degeneration in Parkinson's disease; to investigate the influence of short term treatment with D2 receptor agonists on striatal [ 123 I]β-CIT binding; and to determine the sample size and frequency of SPECT imaging required to demonstrate a significant effect of a putative neuroprotective agent. Methods: A group of 50 early stage Parkinson's disease patients was examined. Two SPECT imaging series were obtained, 12 months apart. The mean annual change in the ratio of specific to non-specific [ 123 I]β-CIT binding to the striatum, putamen, and caudate nucleus was used as the outcome measure. Results: A decrease in [ 123 I]β-CIT binding ratios between the two images was found in all regions of interest. The average decrease in [ 123 I]β-CIT binding ratios was about 8% in the whole striatum, 8% in the putaminal region, and 4% in the caudate region. Comparison of scans done in nine patients under two different conditions—in the off state and while on drug treatment—showed no significant alterations in the expression of striatal dopamine transporters as measured using [ 123 I]β-CIT SPECT. Power analysis indicated that to detect a significant (p < 0.05) effect of a neuroprotective agent with 0.80 power and 30% of predicted protection within two years, 216 patients are required in each group when the effects are measured in the whole putamen. Conclusions: [ 123 I]β-CIT SPECT seems to be a useful tool to investigate the progression of dopaminergic degeneration in Parkinson's disease and may provide an objective method of measuring the effectiveness of neuroprotective treatments. Short term treatment with a D2 agonist does not have a significant influence on [ 123 I]β-CIT binding to dopamine transporters. If the latter finding is replicated in larger groups of patients, it supports the suitability of [ 123 I]β-CIT SPECT for examining the progression of neurodegeneration in patients being treated with D2 receptor agonists.